Focus in Dutch reading: an eye-tracking experiment with heritage speakers of Turkish - van Rijswijk, Remy; Muntendam, Antje; Dijkstra, Ton (Language, cognition and neuroscience, 2017)
This study examines whether heritage speakers of Turkish in the Netherlands interpret focus in written Dutch sentences differently from L1 speakers of Dutch (controls). Where most previous studies examined effects from the dominant L2 on the heritage language, we investigated whether there are effects from the weaker heritage language on the dominant L2. Dutch and Turkish differ in focus marking. Dutch primarily uses prosody to encode focus, whereas Turkish uses prosody and syntax, with a preverbal area for focused information and a postverbal area for background information. In written sentences no explicit prosody is available, which possibly enhances the role of syntactic cues in interpreting focus. An eye-tracking experiment suggests that, unlike the controls, the bilinguals associate the preverbal area with focus and the postverbal area with background information. These findings are in line with transfer from the weaker L1 to the dominant L2 at the syntax-discourse interface.